2008
DOI: 10.2353/ajpath.2008.071128
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial-Peritoneal Interactions during Endometriotic Lesion Establishment

Abstract: The pathophysiology of endometriosis remains unclear but involves a complex interaction between ectopic endometrium and host peritoneal tissues. We hypothesized that disruption of this interaction would suppress endometriotic lesion formation. We hoped to delineate the molecular and cellular dialogue between ectopic human endometrium and peritoneal tissues in nude mice as a first step toward testing this hypothesis. Human endometrium was xenografted into nude mice, and the resulting lesions were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 72 publications
9
104
0
2
Order By: Relevance
“…Interestingly, a recent report also indicates up-regulation of collagen, lumican, and caldesmon at the transcript level in ECE (40). Investigations by others also suggest an increase in total collagen (40,41) as well as the increased presence of collagen VI in endometriotic cysts (42). Caldesmon, an actin-and calmodulin-binding protein, is associated with podosomes.…”
Section: Figurementioning
confidence: 84%
“…Interestingly, a recent report also indicates up-regulation of collagen, lumican, and caldesmon at the transcript level in ECE (40). Investigations by others also suggest an increase in total collagen (40,41) as well as the increased presence of collagen VI in endometriotic cysts (42). Caldesmon, an actin-and calmodulin-binding protein, is associated with podosomes.…”
Section: Figurementioning
confidence: 84%
“…Some authors have previously stated that human endometrial tissues transplanted in mice derive their blood supply from the surrounding vascular network, with the original human vessel simultaneously disappearing as the mouse vessels invade the stroma (Grü mmer 2001, Bruner-Tran et al 2002, Hull et al 2003, Eggermont et al 2005. However, recent studies have revealed the presence of mouse, human, and functional chimeric human-mouse vessels throughout such grafts (Masuda et al 2007, Similarly, host-derived cell types, such as macrophages and myofibroblasts, have been shown to coexist with macrophages from human endometrium embedded in the stroma of immunocompromised mouse xenografts (Hull et al 2008, Guo et al 2011. Such studies reveal an interaction between host and graft at different levels, by which a combined structure capable of responding to different stimuli is created.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis involves complex molecular interactions between endometrial tissue, peritoneal tissue, infiltrating leucocytes, and fibroblasts (Hull et al 2008). In addition, the origin of neovasculature in xenografts remains unclear, which further complicates the analysis of these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the differences in gene expression between the ectopic and eutopic endometrium (17)(18)(19)(20)(21)(22) have found that many genes related to cell adhesion, cell migration, cell proliferation, immune regulation and inflammation are differentially expressed in ectopic vs. eutopic endometrial tissue. In the study by Ohlsson Teague et al (12), it was suggested that c-Jun mRNA expression was significantly increased in endometriosis.…”
Section: Discussionmentioning
confidence: 99%